The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1111/boj.12084
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and biogeography of Ni-hyperaccumulators ofAlyssumsectionOdontarrhena(Brassicaceae) in the central western Mediterranean: evidence from karyology, morphology and DNA sequence data

Abstract: The diversity of Alyssum section Odontarrhena in the central-western Mediterranean region was investigated to elucidate relationships and biogeography of Ni-hyperaccumulators in the group. Karyological, morphometric and molecular phylogenetic analyses were performed on accessions of Ni-hyperaccumulators from serpentine outcrops and non-hyperaccumulators from calcareous-dolomitic soils in the region. Alpine and Apennine populations of A. argenteum, Sardinian A. tavolarae and some Tuscan A. bertolonii had a tetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 56 publications
5
25
0
Order By: Relevance
“…In this study, the existence of three clades (O1, O2 and O3, Fig. ) was supported by the ITS dataset, as well as the ropC1 data (Cecchi et al ), but not by the trnL‐F data.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In this study, the existence of three clades (O1, O2 and O3, Fig. ) was supported by the ITS dataset, as well as the ropC1 data (Cecchi et al ), but not by the trnL‐F data.…”
Section: Discussionsupporting
confidence: 64%
“…Odontarrhena (excluding A. lanigerum) was largely supported as monophyletic by both the ITS and trnL-F MP analyses. This section has also been found to be also supported as a monophyletic group by rpoC1 gene sequences (Cecchi et al 2013). Species of A. sect.…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, ploidy difference is likely to act as an additional isolating mechanism between some populations of this species. All the Iberian populations analysed in this study are diploid, with n = 8 (Fernandes and Queirós, 1973;Küpfer, 1974;Cecchi et al, 2013), but both diploid n = 8 (Küpfer, 1974) and tetraploid n = 16 (Bonnet, 1963;Puech, 1963) populations have been reported in France. All these factors may contribute to gradual divergence between individual populations, and the plants from different populations show some morphological differences.…”
Section: Evolution Of Nickel Hyperaccumulation In Genus Alyssummentioning
confidence: 77%
“…This has led to earlier proposals to raise the serpentine populations of A. serpyllifolium to the status of distinct subspecies, or even separate species (Dudley, 1986a and b,). However, analyses based on chloroplast DNA sequences have been unable to establish clearly resolved relationships between the different A. serpyllifolium populations (Cecchi et al, 2013;Flynn, 2013). In this paper, we have therefore reinvestigated the relationships between serpentine and nonserpentine populations of A. serpyllifolium using population-genetic approaches.…”
Section: Evolution Of Nickel Hyperaccumulation In Genus Alyssummentioning
confidence: 99%
“…In general, the populations in the present study were clustered similarly by the genetic and morphological analyses, with the exception of the populations from MC, CG, and CR. Other studies comparing genetic and morphological variations have reported contrasting results (Kjaer et al ., ; Hatziskakis, Tsiripidis & Papageorgiou, ; Cecchi et al ., ): in a regional analysis of sago palm ( Metroxylon sagu Rottb. ), Kjaer et al .…”
Section: Discussionmentioning
confidence: 99%